Entrance, Construction House - Ghosh, Ayan (2023)
The land on which Construction House stands was lying vacant till 1936 when the plot was acquired by the Walchand Group. Because it came up more than two decades after Ballard Estate was developed, Construction House has a contrasting look, inspired more by the Art Deco style of the late 1930s than the Edwardian Baroque of the early 20th century.